Pre-quake frequency characteristics of Ms ≥7.0 earthquakes in mainland China - Luo, Guofu; Ding, Fenghe; Ma, Heqing; Yang, Mingzhi (Frontiers in Earth Science, 2023)
Seismologists focus on analyzing and capturing medium and short-term impending anomalies of medium and small earthquakes before large earthquakes. The natural orthogonal expansion method can effectively extract small and medium seismicity anomalies in the epicentral region before large earthquakes, which can improve the prediction of large earthquakes. In this study, the frequency range of small earthquakes that occurred in the Chinese mainland before 1980, specifically nine earthquakes with a magnitude of 7 or above, were calculated, and the temporal and spatial anomalies of the frequency fields before the large earthquakes were extracted. The active faults in each large earthquake area (latitude 3 degrees multiplied by longitude 3 degrees) were analyzed to identify the dangerous locations of major earthquakes. In addition, compared with the traditional regional seismicity frequency method, the natural orthogonal expansion method effectively captured the short-term and impending anomalies in the seismic frequency field before large earthquakes. The results of this study can have a significant impact on the analysis of anomalies by frequency field, and make an outstanding contribution to the study of large earthquake prediction.